2021
DOI: 10.1038/s41393-021-00680-y
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the impact of cannabinoids on neurobehavioral outcomes in preclinical models of traumatic and nontraumatic spinal cord injury

Abstract: Study design Systematic review. Objectives To evaluate the impact of cannabinoids on neurobehavioral outcomes in preclinical models of nontraumatic and traumatic spinal cord injury (SCI), with the aim of determining suitability for clinical trials involving SCI patients. Methods A systematic search was performed in MEDLINE and Embase databases, following registration with PROPSERO (CRD42019149671). Studies evaluatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…As of the time of writing, 1 of the SRs has been published and the other is being prepared for submission [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As of the time of writing, 1 of the SRs has been published and the other is being prepared for submission [ 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both SRs were in due reference to the priorities of patients with DCM, expressed through forums including Myelopathy.org, an international myelopathy charity, and the Research Objectives and Common Data Elements for DCM process, an international consensus process to define the research priorities for DCM [13][14][15]. The topics of the reviews were (1) the impact of phosphodiesterase 3 and 4 inhibition on neurobehavioral outcomes in preclinical models of traumatic and nontraumatic spinal cord injury and (2) the role of cannabinoids on modulating neurobehavioral outcomes in preclinical models of traumatic and nontraumatic spinal cord injury [16]. Both reviews were registered on PROSPERO (University of York, United Kingdom; CRD42019150639 and CRD42019149671, respectively).…”
Section: Sr Conceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each rat was placed in an enclosure measuring 1m by 0.5m and observed for 5–10 min for any motor deficits listed on the 21-point BBB scoring scale, where 21 is normal and 0 represents no movement in any of the three leg joints [ 22 ]. Tarlov scoring is a more general gauge of motor function, measuring the degree of paralysis in the hindlimbs within scores of 0–4 [ 53 ]. Tarlov scoring was determined in the same exam period based on the following descriptions: (0) no voluntary movement, (1) perceptible movement at the joint, (2) good joint mobility but the inability to stand, (3) ability to stand and walk, and (4) complete recovery [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies showed an elevation of CBRs in the spinal cord, especially the CB2R, after acute neuropathological conditions such as SCI, neuropathic pain and movement disorder, and amelioration of pain hypersensitivity upon treatment with cannabinoid compounds (Bhatti et al, 2021; Duffy et al, 2021). On the other hand, it was reported that spinal TRPV1 participates in neuropathic pain state maintenance and exacerbation through the extra‐release of glutamate (Choi et al, 2016; Uta et al, 2019).…”
Section: Microglia and Ecs Signaling In The Spinal Cordmentioning
confidence: 99%